Automation of a Combustion Engine-Driven Sprinkler Irrigation Pump in Shallot (Allium ascalonicum) Cultivation - Rosalinda, Rosalinda; Sapsal, Muhammad Tahir; Achmad, Mahmud; Olly Sanny, Hutabarat; Ahmad, Munir; Suhardi, Suhardi (Salaga Journal, 2025)
Sprinkler irrigation control is necessary not only for efficiency but also for reducing bulb rot in shallot cultivation caused by excessive watering. This study developed an Arduino-based automatic control system for a combustion-engine-powered sprinkler irrigation setup to prevent overwatering in shallot farming in Enrekang Regency, Indonesia. The system used a servo motor to adjust the throttle lever of the combustion engine, allowing it to stop pumping the water when the soil moisture level detected by the YL-69 sensor exceeded the optimal threshold. This ensured that the irrigation was applied according to the ideal soil moisture level. The testing included infiltration rate measurement, sprinkler uniformity analysis, sensor calibration, system performance evaluation, and shallot yield assessment. The results showed an average irrigation uniformity coefficient (CU) of 84.34%, with the system operating for 10–28 minutes to maintain soil moisture at no more than 70%. The plot using the control system yielded 140 kg of shallots, whereas the plot without the system produced only 96.2 kg. Additionally, the percentage of rotten shallots in the control plot was 5%, which was significantly lower than that observed in the uncontrolled plot (18%). This system effectively reduced bulb rot, demonstrating its feasibility for optimizing water use and improving crop productivity in areas without access to electricity.